Phorbol esters induce death in MCF-7 breast cancer cells with altered expression of protein kinase C isoforms. Role for p53-independent induction of gadd-45 in initiating death. - J E de Vente; C A Kukoly; W O Bryant; K J Posekany; J Chen; D J Fletcher; P J Parker; G J Pettit; G Lozano; P P Cook (The Journal of Clinical Investigation, 1995)
Protein kinase C (PKC) modulates growth, differentiation and apoptosis in a cell-specific fashion. Overexpression of PKC-alpha in MCF-7 breast cancer cells (MCF-7-PKC-alpha cell) leads to expression of a more transformed phenotype. The response of MCF-7 and MCF-7-PKC-alpha cells to phorbol esters (TPA) was examined. TPA-treated MCF-7 cells demonstrated a modest cytostatic response associated with a G1 arrest that was accompanied by Cip1 expression and retinoblastoma hypophosphorylation. While p53 was detected in MCF-7 cells, evidence for TPA-induced stimulation of p53 transcriptional activity was not evident. In contrast, TPA treatment induced death of MCF-7-PKC-alpha cells. Bryostatin 1, another PKC activator, exerted modest cytostatic effects on MCF-7 cells while producing a cytotoxic response at low doses in MCF-7-PKC-alpha cells that waned at higher concentrations. TPA-treated MCF-7-PKC-alpha cells accumulated in G2/M, did not express p53, displayed decreased Cip1 expression, and demonstrated a reduction in retinoblastoma hypophosphorylation. TPA-treated MCF-7-PKC-alpha cells expressed gadd-45 which occurred before the onset of apoptosis. Thus, alterations in the PKC pathway can modulate the decision of a breast cancer cell to undergo death or differentiation. In addition, these data show that PKC activation can induce expression of gadd45 in a p53-independent fashion. Images